Knee Arthropathy and Bilateral Total Knee Arthroplasty Ratio in Hemophilia A Patients - Levent Bayam; Justine Theaker; Sanat V Shah (Sakarya Tıp Dergisi, 2019)
Objective:This epidemiological study was conducted in the joint haematology-orthopaedics clinic of a university hospital. The aim was to analyse the data in terms of age and radiology of patients with moderate or severe haemophilia A and knee involvement. Materials and Method:This was a retrospective study 49 patients with knee problems out of 130 haemophilia A and musculoskeletal problems. Kellgren-Lawrence (KL) classification was used for radiological assessments of osteoarthritis degree.  Results:KL degree was 3 or 4 for most patients (27/39, 69.23%) in the group. There was statistically a meaningful correlation between KL degree and patients’ age (Spearman’s: rs = 0.512, p = 0.001). There were 7 patients with KL degree 4 at the age of 50 or younger (14.29%).  25 patients in 49(51.02%) had total knee arthroplasty(TKA) and 10(40%) of those was bilateral.  Mean age for bilateral TKA(56.35) was higher than unilateral(49.87). There was a statistically meaningful correlation between patient age and the patients with TKA (Spearman’s: rs = 0.338, p = 0.017). There were 2 revision surgeries out of 35 TKA (5.71%). Most of the patients had prophylactic factor treatment (43, 87.75%). Conclusion: